2021
DOI: 10.1063/5.0042808
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of multiple plasma polarization modes in particles–multilayer film system for surface-enhanced Raman scattering

Abstract: Since localized surface plasmon (LSP) is capable of generating strong electromagnetic fields, it has achieved extensive applications in surface-enhanced Raman scattering (SERS). As opposed to this, surface plasmon polariton (SPP) has been rarely employed for its weak electric field enhancement. The present study proposed an Ag nanoparticles (AgNPs) and multilayer Au/Al2O3 film (MLF) hybrid system, acting as an efficient SERS substrate by coupling LSPs and SPPs resonances. The dispersion relationship indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…The nature of coupled plasmonic nanoparticles allows for the localized enhancement of plasmon strength, allowing for nanoprecise chemical transformations or material grafting. In particular, chemical transformations can occur in spatially restricted areas with a more pronounced concentration of the plasmon EF. This method of spatially selective modification clears the way for the creation of a whole series of improved plasmonic substrates with broader functionality in the sensorics field and chemical technology. In this work, we demonstrated the ability to utilize SPP–LSP plasmonic coupling for nanoprecise chemical transformation for the first time. To model the chemical transformation, we used the well-known dimerization of amino groups and the related azo-bridge formation reaction, which lead to the spatially selective immobilization of plasmon-active Au nanoparticles (AuNPs) on the surface of the Au grating.…”
Section: Introductionmentioning
confidence: 91%
“…The nature of coupled plasmonic nanoparticles allows for the localized enhancement of plasmon strength, allowing for nanoprecise chemical transformations or material grafting. In particular, chemical transformations can occur in spatially restricted areas with a more pronounced concentration of the plasmon EF. This method of spatially selective modification clears the way for the creation of a whole series of improved plasmonic substrates with broader functionality in the sensorics field and chemical technology. In this work, we demonstrated the ability to utilize SPP–LSP plasmonic coupling for nanoprecise chemical transformation for the first time. To model the chemical transformation, we used the well-known dimerization of amino groups and the related azo-bridge formation reaction, which lead to the spatially selective immobilization of plasmon-active Au nanoparticles (AuNPs) on the surface of the Au grating.…”
Section: Introductionmentioning
confidence: 91%
“…A sharp EM field generated within the vicinity of plasmonic NSs plays a crucial role to trigger the huge enhancement in scattered Raman signal. Several studies regarding these intrinsic hotspots [85][86][87][88] of the plasmonic nanoentities have emerged out as hot topic of research interest. The interesting phenomena of additional enhancement in SERS signal can be justified by exploring the two-body configuration constituting the AgNS2 interfaced with sub-30 nm gold coatings.…”
Section: Cooperative Enhancement In the Sers Signalmentioning
confidence: 99%
“…They have demonstrated 'Au film-molecules-AgNPs' combined system approach, that turned out to be effective in offering boosted SERS signal for R6G molecule and also similar to a two-body configuration [87]. Liu et al also reported significant increase in the Raman intensity from a hybrid system consisting of Ag NPs with multilayer Au/Al 2 O 3 film [88]. In this spectrum of work, we believe that the instigation of the huge field-enhancement from the two-body integrated system (nm-scale Au coating + nm Ag NS) can be explained on the basis of LSP coupling effect unified from both plasmonic systems.…”
Section: Cooperative Enhancement In the Sers Signalmentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS) technology is extensively used in areas such as food safety, environmental conservation, and biomedical sensors and measurement, due to its unique superiorities like sensitive detection and nondestructive analysis. The local surface plasmon resonance (LSPR) of noble metal (Au, Ag, and Cu) nanoparticles excited by the incident laser enhances the Raman signal of the molecules on substrates, which usually leads to a significant SERS enhancement. However, SERS applications based on metals in biological and medical science are limited by high cost, poor biocompatibility, uniformity, and inferior stability. The chemical enhancement mechanism (CM) based on semiconductor materials can solve the problems mentioned above. , Moreover, CM-SERS is a short-range effect and the probe molecules are required to be close to the substrate, the interaction between many probe molecules and the SERS substrate can be analyzed by CM-SERS enhancement.…”
Section: Introductionmentioning
confidence: 99%